2017
DOI: 10.1002/jsfa.8255
|View full text |Cite
|
Sign up to set email alerts
|

Guayusa (Ilex guayusa L.) new tea: phenolic and carotenoid composition and antioxidant capacity

Abstract: Therefore, blanched guayusa has potential for product development as a functional ingredient in the food industry. © 2017 Society of Chemical Industry.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
29
0
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(39 citation statements)
references
References 43 publications
2
29
0
3
Order By: Relevance
“…guayusa have previously been shown to contain caffeine as well as other methylxanthine derivatives like theobromine and theophylline. 28 The composition of the I. guayusa teas shown here was similar to that previously reported by García-Ruiz et al 17…”
Section: Lc-ms/ms Evaluation Of Unfermented and Fermented I Guayusa supporting
confidence: 89%
See 1 more Smart Citation
“…guayusa have previously been shown to contain caffeine as well as other methylxanthine derivatives like theobromine and theophylline. 28 The composition of the I. guayusa teas shown here was similar to that previously reported by García-Ruiz et al 17…”
Section: Lc-ms/ms Evaluation Of Unfermented and Fermented I Guayusa supporting
confidence: 89%
“…Mass spectrometry analysis of unfermented and fermented I. guayusa teas in the negative ionization mode, revealed that the teas are rich in phenolic compounds particularly refers to compounds tentatively identified in Table 1. 9,17,26 Although the unfermented tea was more complex, the fermented tea showed similar bioactivities suggesting that caffeoylquinic acid derivatives are the major determinants of the antioxidant and anti-inflammatory activity observed here for the tea preparations. These types of compounds have previously shown antioxidant and anti-inflammatory activity.…”
Section: Lc-ms/ms Evaluation Of Unfermented and Fermented I Guayusa mentioning
confidence: 70%
“…Hence, their regulation in different tissues was controlled by different developmental cues. Numerous reports have highlighted antioxidant property of carotenoids (El-Agamey et al, 2004; Das and Roychoudhury, 2014; Aquino et al, 2016; García-Ruiz et al, 2017). Radical scavenging assay (inhibition of DPPH) showed ripe pulp extract has significantly higher antioxidant activity as compared to the unripe pulp.…”
Section: Discussionmentioning
confidence: 99%
“…They are involved in signaling process and scavenging of free radicals during the stress management (El-Agamey et al, 2004; Aquino et al, 2016; García-Ruiz et al, 2017). Oxidized carotenoids (apocarotenoids) lead to produce abscisic acid (ABA), strigolactone, β–cyclocitral and β-ionone which subsequently assist plants to adapt in different stress conditions (Pogson et al, 2008; Havaux, 2014; Hou et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…has been consumed as a herbal tea for hundreds of years in western Amazon regions including Colombia, Ecuador, Peru and Bolivia, and ethnographic studies broadly report claims of its stimulant and health properties [1,2,3]. Further laboratory studies of guayusa's chemical composition provide scientific support for those claims based on its caffeine, amino acid and antioxidant composition [4,5,6]. Considered to be a domesticated plant, its reproduction is only known to occur through human propagation from hardwood stem cuttings.…”
Section: Introductionmentioning
confidence: 99%